Adaptation of the Treatment Satisfaction with Medicines Questionnaire (SATMED-Q) to Indonesian for Chronic Diseases Patients - Viviandhari, Daniek; Wulandari, Nora; Nurhasnah, Nurhasnah (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: National data indicate an increase in chronic disease prevalence. Therapeutic outcomes need to be assessed based on the aspects of the patient’s psychology, including treatment satisfaction. In Indonesia, no native or cross-culturally adapted treatment satisfaction tool is available and validated for chronic disease patients.Objectives: The study is intended to conduct cross-cultural translation and adaptation of the Treatment Satisfaction with Medicines Questionnaire (SATMED-Q) into Indonesian and to evaluate the questionnaire’s reliability and validity in the Indonesian context.Methods: SATMED-Q translation and adaptation were conducted following a systematic procedure: forward translation, synthesis, backward translation, expert committee review, and pre-testing. The samples were hypertension and type 2 diabetes mellitus patients at the primary health care center. The internal consistency and known-group validity were analyzed statistically.Results: A total of 45 participants were involved in the research to assess the reliability and validity of the translated questionnaire. Some grammatical changes were made on the forward translation, the back translation, and the expert committee review stage. The major changes were the definition of the Likert-type scale on each domain. The reliability test showed good consistency (Cronbach’s alpha=0.842). Certain factors (gender and working status) showed known group validity, but not the number of antihypertensive or antidiabetic medications. Compared to individuals who took two medications, people who took one medicine indicated less satisfaction with their treatment.Conclusion: The translation and cross-cultural adaptation of the SATMED-Q to Indonesian was satisfactory. The Indonesian version of SATMED-Q was a reliable and valid instrument to assess treatment satisfaction.